Comparison of the pervaporation separation of a water-acetonitrile mixture with zeolite-filled sodium alginate and poly(vinyl alcohol)-polyaniline semi-interpenetrating polymer network membranes - Naidu, B. V. K.; Bhat, S. D.; Sairam, M.; Wali, A. C.; Sawant, D. P.; Halligudi, Shivaraj B.; Mallikarjuna, N. N.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The pervaporation (PV) separation performance of ZSM-5- and Na-Y-type zeolite-filled sodium alginate (NaAlg) membranes were compared with those of pure NaAlg and semi-interpenetrating polymer network (semi-IPN) membranes of poly(vinyl alcohol) (PVA) with polyaniline (PANI) for the dehydration of acetonitrile. The PV separation characteristics of the zeolite-filled membranes showed a dependence on the nature of the zeolites. The variation of the acidity function of the ZSM-5 zeolite had an influence on the flux and selectivity of the membranes when compared to unfilled membranes. The crosslinked membranes were characterized by differential scanning calorimetry, X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. Increasing the PANI content of the semi-IPN network increased the separation selectivity. Among the NaAlg membranes, the plain NaAlg membrane showed the highest selectivity of 414 at 30 mass % water in the feed mixture, whereas the Na-Y- and ZSM-5 (40)-filled NaAlg membranes exhibited much lower values of selectivity, that is, 7.3 and 4.3, respectively for 30 mass % water in the feed. When the flux and selectivity data of ZSM-5 (250)-filled NaAlg membranes were compared with that of Na-Y- or ZSM-5 (40)-filled NaAlg membranes, a noticeable increase in the selectivity for the ZSM-5 (250)filled NaAlg membrane was observed, but a somewhat comparable flux was observed compared to the plain NaAlg membrane. For the first time, PANI was polymerized with PVA to yield a semi-IPN. The total flux and water flux increased systematically, whereas the selectivity decreased greatly from 251.87 to 5.95 with increasing amounts of water in the feed. (c) 2005 Wiley Periodicals, Inc.
Keywords: Diffusion; interpenetrating network (IPN); zeolites

Miscibility of chitosan-hydroxyethylcellulose blends in aqueous acetic acid solutions at 35 degrees C - Wali, A. C.; Naidu, B. V. K.; Mallikarjuna, N. N.; Sainkar, S. R.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The miscibility of blends of chitosan and hydroxyethylcellulose in a 2% acetic acid solution was studied by viscometry, densitometry, and refractometry at 35 degrees C. The data suggest that the blends were completely miscible in all proportions. Further, the membranes were fabricated from concentrated blend solutions. The solid-state compatibility of the blends was confirmed by scanning electron microscopy. (c) 2005 Wiley Periodicals, Inc.
Keywords: blends; miscibility; refractive index; viscosity

Mesoporous molecular sieve (MCM-41)-filled sodium alginate hybrid nanocomposite membranes for pervaporation separation of water-isopropanol mixtures - Bhat, S. D.; Naidu, B. V. K.; Shanbhag, G.; Halligudi, Shivaraj B.; Sairam, M.; Aminabhavi, Tejraj M. (Separation of Purification Technology, 2006)
Sodium alginate (NaAlg) and the inesoporous molecular sieve (MCM-41)-filled NaAlg nanocomposite membranes have been prepared by solution casting and crosslinked with glutaraldehyde. Pervaporation performance of the MCM-41-filled NaAlg membranes has been tested and compared with plain NaAlg membrane for dehydrating isopropanol at 30 degrees C. In the studied feed composition range of 10-50 mass% of water, 20 mass% MCM-41-loaded NaAlg membrane gave the highest selectivity ranging between 29,991 and 3332 in the range of feed water compositions of 10-50 mass%. Flux for the plain NaAlg membrane ranged between 0.067 and 0.340 kg/(m(2)h), while for 20 mass% MCM-41-filled NaAlg membrane, flux increased to 0.110 and 0.555 kg/(m(2)h). To the best of our knowledge, this is the first study reported on the membrane forming properties of an admixed hybrid composite of a mesoporous molecular sieve (MCM-41) with NaAlg used in dehydration of isopropanol, yielding high selectivity to water at higher loadings of the molecular sieve as a filler. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: flux and selectivity; nanocomposite membranes; pervaporation; sodium alginate; water-isopropanol

Development of transdermal drug-delivery films with castor-oil-based polyurethanes - Shelke, Namdev B.; Sairam, Malladi; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
Two different types of polyurethanes (PUs) were prepared with castor oil, ethylene glycol, isophorene diisocyanate and castor oil, and isophoren diisocyanate and poly(ethylene glycol) (400 or 600). PU films were prepared and characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, and gel permeation chromatography. We prepared transdermal patches by loading different amounts of drug, plasticizer, and penetration enhancer. In vitro drug permeability through the castor-oil-based aliphatic PU patches was examined with a Keshary-Chien diffusion cell. The effect of castor oil on the film-forming properties and the effect of penetration enhancers on diffusion characteristics of indomethacin (IDM) drug through the castor-oil-based PU were investigated. Prolonged release of IDM was observed from the prepared PU patches. In vitro drug diffusion revealed that slow and prolonged release of IDM was achieved in the absence of penetration enhancers. The use of penetration enhancers showed a significant effect on drug diffusion. (c) 2006 Wiley Periodicals, Inc.
Keywords: castor oil; drug delivery; polyurethane; transdermal

Preparation and evaluation of cellulose acetate butyrate and poly(ethylene oxide) blend microspheres for gastroretentive floating delivery of repaglinide - Rokhade, Ajit P.; Patil, Sangamesh A.; Belhekar, Anagha A.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
In this study, hollow microspheres of cellulose acetate butyrate (CAB) and poly(ethylene oxide) (PEO) were prepared by emulsion-solvent evaporation method. Repaglinide was successfully encapsulated into floating microspheres. Various formulations were prepared by varying the ratio of CAB and PEO, drug loading and concentration of poly(vinyl alcohol) (PVA) solution. Encapsulation of the drug up to 95% was achieved. The microspheres tend to float over the simulated gastric media for more than 10 h. The micromeritic properties of microspheres reveal the excellent flow and good packing properties. The % buoyancy of microspheres was found to be up to 87. SEM showed that microspheres have many pores on their surfaces. Particle size ranges from 159 to 601 mu m. DSC and X-RD revealed the amorphous dispersion in the polymer matrix. In vitro release experiments were performed in simulated gastric fluid. In vitro release studies indicated the dependence of release rate on the extent of drug loading and the amount of PEO in the microspheres; slow release was extended up to 12 h. The release data were fitted to an empirical equation to compute the diffusional exponent (n), which indicated that the release mechanism followed the non-Fickian trend. (C) 2007 Wiley Periodicals, Inc.
Keywords: cellulose acetate butyrate; Controlled release; floating drug delivery; microspheres; repaglinide

Synthesis and characterization of novel polyurethanes based on 4,4 `-[1,4-phenylenedi-diazene-2,1-dlyl] bis(2-carboxyphenol) and 4,4 `-[1,4-phenylenedi-diazene-2,1-diyl] bis(2-chlorophenol) hard segments - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Reactive & Functional Polymers, 2007)
Eight novel polyurethanes (PUs) based on 4,4'-[1,4-phenylenedi-diazene-2,1-diyl]bis(2-carboxyphenot) and 4,4'-[1,4phenylenedi-diazene-2,1-diyl]bis(2-chloro- phenol) as hard segments with four diisocyanates viz., 4,4-diphenyl-methane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate were prepared. Structural and thermal characterization of the segmented PUs were determined by FT-IR, UV spectrophotometry, fluoroscence spectroscopy, H-1 NMR, C-13 NMR spectroscopy and DTA/TGA analysis. All the PUs contain domains of semi-crystalline and amorphous structures, as indicated by X-ray diffraction. PUs were soluble in polar aprotic solvents like N-methyl-2-pyrrolidone (NMP), dimethyl formamide (DMF) and dimethylsulfoxide (DIVISO). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: azo polymers; fluorescence; hard segments; Morphology; phase separation; polyurethanes; spectroscopy; Thermal properties

Synthesis, characterization, and acoustic properties of new soluble polyurethanes based on 2,2 `-[1,4-phenylenebis(nitrilomethylylidene)diphenol and 2,2 `-[4,4 `-methylene-di-2-methylphenylene-1,1 `-bis(nitrilomethylylidene)]diphenol - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
Eight novel polyurethanes based on 2,2'-[1,4-phenylenebis(nitrilomethylylidene)]diphenol and 2,2-[4,4'methylene-di-2-methylphenylene-1,1'-bis(nitrilomethylylidene) ]diphenol acting as hard segments with two aromatic and two aliphatic diisocyanates (4,4'-diphenytmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) were prepared and characterized with Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1-NMR and C-13-NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis. All the polyurethanes contained domains of semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties and solubility parameters were calculated with the group contribution method. (c) 2007 Wiley Periodicals, Inc.
Keywords: infrared spectroscopy; NMR; phase behavior; polyurethanes; Thermal properties

Synthesis and characterization of novel schiff base polyurethanes - Raghu, A. V.; Gadaginamath, G. S.; Jeong, Han Mo; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2009)
Eight different types of novel polyurethanes (PUs) were synthesized through the polyaddition reaction of 4,4'-(ethane-1,2-diylidenedinitrilo)diphenol and 4,4'(pentane-1,5-diylidenedinitrilo)diphenol with four different diisocyanates: 4,4'-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate. The resulting PUs were soluble in polar, aprotic solvents. Structures of the diols and PUs were established with Ultraviolet-visible, fluorescence, Fourier transform infrared (FTIR), (1)H-NMR, and (13)C-NMR spectroscopy data. FTIR and NMR spectral data indicated the disappearance of both hydroxyl and isocyanate groups in the PUs. The thermal properties were investigated with thermogravimetry and differential scanning calorimetry. The weight losses, glass transitions, onset temperatures, and crystalline melting temperatures were measured. All the PUs exhibited semicrystalline and amorphous morphologies, as indicated by X-ray diffraction. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 113: 2747-2754, 2009
Keywords: amorphous; Morphology; polyurethanes; synthesis; Thermal properties